Factor Analysis at Item Test Conceptual Understanding Of Numerical Method - Mahendra, I Wayan Eka; Rini Purwati, Ni Kadek (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Factor analysis at item test conceptual understanding of numerical method aims to find out whether the conceptual understanding indicators used can confirm a construct and ensure that the test is complied with the indicator. Data analysis is done using confirmatory factor analysis. Â Based on data analysis, one factor is formed with Eigen value 2.352 and variation is 58.8%. This result shows that the indicators of conceptual understanding ability are valid, and the test prepared in accordance with the indicators of conceptual understanding ability.